Preparing Indonesian civil engineering graduates for the world of work. Issue 4 (August 2022) - Fitriani, Heni; Ajayi, Saheed
This study investigates numerous competencies expected from civil engineering graduates based on employers' perspectives in Indonesia to provide an understanding of employers' requirements related to knowledge, skills and personal traits. Using the employers of civil engineering graduates as the study population, both qualitative and quantitative approaches were adopted for data collection and analysis, following an exploratory sequential mixed method design. The results, developed from a factor analysis, show that the underlying skills, knowledge and general traits that can give competitive advantages for graduates include 10 elements. The most significant components consist of interpersonal management skills, personality traits and entrepreneurial and business skills. As the first two factors, categorised as soft skills associated with traits and character, were the most important, the implication is that employers tend to prioritise building strong characters, even when recruiting or selecting employees with limited technical skills normally obtained during university studies. Other competencies expected of Indonesian civil engineering graduates discussed in the article include digital skills, as well as core knowledge of civil engineering, such as design and geotechnics skills. The findings will benefit universities seeking to enhance their graduates' employability as well as students who are hoping to be ahead of the game. The article also provides insights for civil engineering employers who may want to understand the key skills and competencies in demand by other employers of civil engineering graduates in Indonesia.